2018
DOI: 10.1089/jir.2018.0061
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Inhibits Chemokine Expression Through the AMPK/NF-κB Signaling Pathway

Abstract: Inflammation is mediated by cytokines and chemokines, which are considered targets of inflammatory diseases. Mounting evidence has demonstrated the anti-inflammatory benefits of metformin. However, the underlying mechanisms are not completely understood. In this study, we aim to elucidate the regulatory effects of metformin on chemokine expression and the possible mechanisms using RAW264.7 cells, a mouse macrophage cell line, as a model. First, we treated the cells with lipopolysaccharide (LPS), and found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Increasing evidence have shown that MET exerts its anti-oxidative and anti-inflammatory activities via suppression of NF-κB while activation of Nrf2 signaling pathways ( Chiang et al., 2017 ; Ye et al., 2018 ). We next wan to elucidate whether NF-κB and Nrf2 signaling pathways are independent or crosstalk with each other under the GDM condition.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence have shown that MET exerts its anti-oxidative and anti-inflammatory activities via suppression of NF-κB while activation of Nrf2 signaling pathways ( Chiang et al., 2017 ; Ye et al., 2018 ). We next wan to elucidate whether NF-κB and Nrf2 signaling pathways are independent or crosstalk with each other under the GDM condition.…”
Section: Resultsmentioning
confidence: 99%
“…There are several possible mechanisms to explain how the activators of AMPK could suppress the functions of MDSCs in cancer therapy. For instance, it is known that AMPK activators downregulate the chemokine signaling in macrophages [189, 190] which might impair the chemokine-driven accumulation of MDSCs into tumors. Given that AMPK activators have displayed beneficial effects in cancer combination therapies [191], it would be important to clarify whether they could improve cancer immunotherapies by inhibiting the MDSC-induced immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…After IκB is degraded, the NF-κB complex is phosphorylated and translocated to the nucleus. Then, various mRNAs including MMP3 , MMP13 , and COX-2 are upregulated [ 60 , 62 , 63 ]. Activation of the NF-κB signaling pathway leads to the degradation of articular cartilage and increases the expression of catabolic factors that can lead to arthritis [ 64 ].…”
Section: Discussionmentioning
confidence: 99%